CLINICAL UNDERSTANDING OF MUTRAVAHA SROTO VIKARA WITH SPECIAL REFERENCE TO SEQUENTIAL ARRANGEMENT OF MUTRASHMARI (URINARY CALCULUS) AS PER SUSHRUTA - Puripanda, *S.Kamalakar; M, Chetan (International Journal of Ayurveda and Pharma Research, 2016)
Mutrashmari is one of the common disease of the Mutravaha Srotas. The Mahagadas are difficult to cure due to their Ashraya in Marma Sthana and Involvement of Bahudoshas etc. Sushruta and Vagbhata considered Ashmari as one among the Asta Mahagada. The classical Lakshana of Mutrashmari is Vedana with Sanga of Mutra along with vitiated Dosa in Mutravaha Srotas. Acharya Susrutha has explained four types of Mutrashmari with sequential arrangement like Kaphaja (Kidney Stones), Vataja (Uretric Stones), Pittaja (Vesicle Stones) and Shukraja. This disease is classified on the basis of signs and symptoms of involved Dosa like Kaphaja (Dull ache), Vaataja (Severe pain), Pittaja (Burning type of pain) in different part of Mutravaha Srotas. According to contemporary science also the classification of calculus depends on mainly signs and symptoms. Intension of this paper is to highlight the concept of clinical understanding the sequence of Mutrashmari (Urinary Calculus) classification as per Sushruta with different case presentations.